The Identification and Genetic Characterization of Parechovirus Infection Among Pediatric Patients With Wide Clinical Spectrum in Chongqing, China - Zhang, Xiao-Ai; Zhao, Rui-Qiu; Chen, Jin-Jin; Yuan, Yang; Tang, Xiang; Zhou, Zi-Wei; Ren, Luo; Lu, Qin-Bin; Wang, Yu-Na; Zhang, Hai-Yang; Zhang, Pan-He; Fang, Li-Qun; et al. (Frontiers in Microbiology, 2021)
Human parechoviruses (HPeVs) are important causes of infection in children. However, without a comprehensive and persistent surveillance, the epidemiology and clinical features of HPeV infection remain ambiguous. We performed a hospital-based surveillance study among three groups of pediatric patients with acute respiratory infection (Group 1), acute diarrhea (Group 2) and Hand, foot and mouth disease (Group 3) in Chongqing, China from 2009-2015. Among totally 10212 tested patients, 707 (6.92%) were positive for HPeV, with the positive rates differing significantly among three groups (Group 1, 3.43%; Group 2, 14.94%; Group 3, 3.55%; P < 0.001). The co-infection with other pathogens was detected in 75.2% (531/707) of HPeV-positive patients. Significant negative interaction between HPeV and Parainfluenza virus (PIV) (P = 0.046, OR= 0.59, 95% CI = 0.34-0.98) and positive interactions between HPeV and Enterovirus (EV) (P = 0.015, OR = 2.28, 95% CI = 1.23-4.73) were identified. Among 707 HPeV-positive patients, 592 (83.73%) were successfully sequenced, and 10 genotypes were identified, with HPeV1 (n = 396), HPeV4 (n = 86) and HPeV3 (n = 46) as the most frequently seen. The proportion of genotypes differed among three groups (P < 0.001), with HPeV1 and HPeV4 overrepresented in Group 2 and HPeV6 overrepresented in Group 3. The spatial patterns of HPeV genotypes disclosed more close clustering of the currently sequenced strains than those from other countries/regions, although they were indeed mixed. Three main genotypes (HPeV1, HPeV3 and HPeV4) had shown distinct seasonal peaks, highlighting a bi-annual cycles of all HpeV and two genotypes (HPeV 1 and HPeV 4) with peaks in odd-numbered years, whereas with peaks in even-numbered years HPeV3. Significantly higher HPeV1 viral loads were associated with severe diarrhea in Group 2, (P = 0.044), while associated with HPeV single infection than HPeV-EV coinfection among HFMD patients (P = 0.001). It’s concluded that HPeV infection was correlated with wide clinical spectrum in pediatric patient, with a high variety of genotypes determined. Still no clinical significance can be confirmed, which warranted more molecular surveillance in the future.